Micro- and nano bio-based delivery systems for food applications: In vitro behavior - de Souza Simões, Lívia; Madalena, Daniel A.; Pinheiro, Ana C.; Teixeira, José A.; Vicente, António A.; Ramos, Óscar L. (Advances in colloid and interface science, 2017)
Micro- and nanoencapsulation is an emerging technology in the food field that potentially allows the improvement of food quality and human health. Bio-based delivery systems of bioactive compounds have a wide variety of morphologies that influence their stability and functional performance. The incorporation of bioactive compounds in food products using micro- and nano-delivery systems may offer extra health benefits, beyond basic nutrition, once their encapsulation may provide protection against undesired environmental conditions (e.g., heat, light and oxygen) along the food chain (including processing and storage), thus improving their bioavailability, while enabling their controlled release and target delivery. This review provides an overview of the bio-based materials currently used for encapsulation of bioactive compounds intended for food applications, as well as the main production techniques employed in the development of micro- and nanosystems. The behavior of such systems and of bioactive compounds entrapped into, throughout in vitro gastrointestinal systems, is also tracked in a critical manner. Comparisons between various in vitro digestion systems (including the main advantages and disadvantages) currently in use, as well as correlations between the behavior of micro- and nanosystems studied through in vitro and in vivo systems were highlighted and discussed here for the first time. Finally, examples of bioactive micro- and nanosystems added to food simulants or to real food matrices are provided, together with a revision of the main challenges for their safe commercialization, the regulatory issues involved and the main legislation aspects. [Display omitted] •Micro- and nanoencapsulation is an emerging technology in the food industry.•Novel delivery systems for food applications can be produced by bio-based materials.•Design of bio-based delivery systems can be tailored by processing conditions.•Bio-based delivery systems allow incorporation of bioactives offering extra benefits.•In vitro models are crucial to understand the behavior of bio-based delivery systems.